An Act prescribing the rules and conduct to be observed with respect to Negroes and other Slaves of this territory, in A General Digest of the Acts of the Legislature of Louisiana, Passed from the Year 1804 to 1827, at 103-04 (1828) - (:unkn) unknown (My University, 1806)
19: No slave shall, by day or by night, carry any visible or hidden arms, not even with a permission for so doing, and in case any person or persons shall find any slave or slaves, using or carrying such fire arms, or any offensive weapons of any other kind, contrary to the true meaning of this act, he, she or they, lawfully, may seize and carry away such fire arms, or other offensive weapons
Keywords: ENSLAVED PERSONS & OTHER MINORITIES